Angiogenesis in Gynecological Cancers: Role of Neurotrophins - Garrido, Maritza P.; Torres, Ignacio; Vega, Margarita; Romero, Carmen (Frontiers in Oncology, 2019)
Angiogenesis, or generation of new blood vessels from other pre-existing, is a key process to maintain the supply of nutrients and oxygen in tissues. Unfortunately, this process is exacerbated in pathologies such as retinopathies and cancers with high angiogenesis as ovarian cancer. Angiogenesis is regulated by multiple systems including growth factors and neurotrophins. One of the most studied angiogenic growth factors is the vascular endothelial growth factor (VEGF), which is overexpressed in several cancers. It has been recently described that neurotrophins could regulate angiogenesis through direct and indirect mechanisms. Neurotrophins are a family of proteins that include nerve growth factor (NGF), brain-derived growth factor (BDNF) and neurotrophins 3 and 4/5 (NT 3, NT 4/5). These molecules and their high affinity receptors (TRKs) regulate the development, maintenance and plasticity of the nervous system. Furthermore, it was recently described that they display essential functions in non-neuronal tissues, such as reproductive organs among others. Studies have shown that several types of cancer overexpress neurotrophins such as NGF and BDNF, which might contribute to tumor progression and angiogenesis. Besides, in recent years the FDA has approved the use of pharmacologic inhibitors of pan-TRK receptors in patients with TRKs fusion-positive cancers. In this review, we discuss the mechanisms by which neurotrophins stimulate tumor progression and angiogenesis, with emphasis on gynecological cancers.